Sedimentology of the tide-dominated Jurassic Lajas Formation, Neuquen Basin, Argentina - Mcllroy, D.; Flint, S.; Howell, J.; Timms, Nicholas Eric (Geological Society of London, 2005)
Tidal depositional systems are often interpreted as lowstand/transgressive estuarine deposits within sequences that are either wave or river dominated during highstand times. The Middle Jurassic Lajas Formation of the Neuquen Basin, Argentina, comprises 600 m of well-exposed tide-dominated facies deposited within four unconformity bounded sequences, spanning approximately 4.5 Ma. Facies associations include tide dominated deltas, sandy-heterolithic tidal channel fills and extensive progradational tidal-flat successions, which are locally cut by heterolithic tidal channel fills. Despite the narrow bathymetric depositional range and the complex facies variability, flooding surfaces can be defined and mapped along a 48 km-long outcrop belt. These flooding surfaces allow definition of three distinct types of parasequence that exhibit coarsening-upwards, finingupwards and coarsening- to fining-upwards motifs. Sequence boundaries are marked by widespread, but shallow, incision, and the juxtaposition of stacked fluvial/tidal channel fills on a variety of subtidal and intertidal facies. Unconventional grain-size changes at sequence boundaries can occur where basin ward facies shifts are marked by juxtaposition of heterolithic-argillaceous intertidal/supratidal mudflat deposits on subtidal sandflat facies. The maintenance of macrotidal conditions through complete base-level cycles is interpreted as being due to the structural topography inherited from rifting, causing the whole sub-basin to behave as a structurally controlled embayment.